Answer:
256
Step-by-step explanation:
64*4
(60*4)+(4*4)
240+16
256
you could also take a different approach--
64=4^3
4^3*4=4^4
4^4=16^2=256
f^3+11g-4hf 3 +11g−4hf, cubed, plus, 11, g, minus, 4, h when f=3f=3f, equals, 3, g=2g=2g, equals, 2 and h=7h=7h, equals, 7.
Alik [6]
Given:
The expression is:
![f^3+11g-4h](https://tex.z-dn.net/?f=f%5E3%2B11g-4h)
The given values are
.
To find:
The value of the given expression for the given values.
Solution:
We have,
![f^3+11g-4h](https://tex.z-dn.net/?f=f%5E3%2B11g-4h)
After substituting
, we get
![f^3+11g-4h=(3)^3+11(2)-4(7)](https://tex.z-dn.net/?f=f%5E3%2B11g-4h%3D%283%29%5E3%2B11%282%29-4%287%29)
![f^3+11g-4h=27+22-28](https://tex.z-dn.net/?f=f%5E3%2B11g-4h%3D27%2B22-28)
![f^3+11g-4h=49-28](https://tex.z-dn.net/?f=f%5E3%2B11g-4h%3D49-28)
![f^3+11g-4h=21](https://tex.z-dn.net/?f=f%5E3%2B11g-4h%3D21)
Therefore, the value of the given expression is 21.
Answer: 30
Step-by-step explanation: when you look at the x value of 9, the y value on the best fit line would be 30